The human aortic endothelium undergoes dose-dependent DNA methylation in response to transient hyperglycemia - Pepin, Mark; Schiano, Concetta; Miceli, Marco; Benincasa, Giuditta; Mansueto, Gelsomina; Grimaldi, Vincenzo; Soricelli, Andrea; Wende, Adam R.; Napoli, Claudio (Experimental cell research, 2021)
Background - Glycemic control is a strong predictor of long-term cardiovascular risk in patients with diabetes mellitus, and poor glycemic control influences long-term risk of cardiovascular disease even decades after optimal medical management. This phenomenon, termed glycemic memory, has been proposed to occur due to stable programs of cardiac and endothelial cell gene expression. This transcriptional remodeling has been shown to occur in the vascular endothelium through a yet undefined mechanism of cellular reprogramming. - Methods - In the current study, we quantified genome-wide DNA methylation of cultured human endothelial aortic cells (HAECs) via reduced-representation bisulfite sequencing (RRBS) following exposure to diabetic (250 mg/dL), pre-diabetic (125 mg/dL), or euglycemic (100 mg/dL) glucose concentrations for 72 h (n = 2). - Results - We discovered glucose-dependent methylation of genomic regions (DMRs) encompassing 2199 genes, with a disproportionate number found among genes associated with angiogenesis and nitric oxide (NO) signaling-related pathways. Multi-omics analysis revealed differential methylation and gene expression of VEGF (↑5.6% DMR, ↑3.6-fold expression), and NOS3 (↓20.3% DMR, ↓1.6-fold expression), nodal regulators of angiogenesis and NO signaling, respectively. - Conclusion - In the current exploratory study, we examine glucose-dependent and dose-responsive alterations in endothelial DNA methylation to examine a putative epigenetic mechanism underlying diabetic vasculopathy. Specifically, we uncover the disproportionate glucose-dependent methylation and gene expression of VEGF and NO signaling cascades, a physiologic imbalance known to cause endothelial dysfunction in diabetes. We therefore hypothesize that epigenetic mechanisms encode a glycemic memory within endothelial cells.